The British Board of Trade's Investigations into Cost of Living - Mitchell, Wesley C. (Quarterly Journal of Economics, 1909)
Cost of Living of the Working Classes. Report of an Enquiry by the Board of Trade into Working Class Rents, Housing and Retail Prices, together with the Standard Rates of Wages prevailing in certain occupations in the principal towns of the United Kingdom. London, 1908. [Cd. 3864.] Price 6s. Pages liii + 616. Industrial. Cost of Living in German Towns. Report of an Enquiry by the Board of Trade into Working Class Rents, Housing and Retail Prices, together with the Rates of Wages in certain occupations in the principal industrial towns of the German Empire. London, 1908. [Cd. 4032.] Price 4s. 11d. Pages lxi + 548.